2018
DOI: 10.1111/jiec.12774
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Batteries in the Future Swiss Electricity Supply System: A Consequential Environmental Assessment

Abstract: Summary Stationary batteries are projected to play a role in the electricity system of Switzerland after 2030. By enabling the integration of surplus production from intermittent renewables, energy storage units displace electricity production from different sources and potentially create environmental benefits. Nevertheless, batteries can also cause substantial environmental impacts during their manufacturing process and through the extraction of raw materials. A prospective consequential life cycle assessmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 80 publications
0
31
0
Order By: Relevance
“…Among the studies, 15 were marked for closed-loop approximation, including both Sanfélix et al [19] and Sanfélix et al [52], who argue for substitution in their attributional study setup. In contrast, only one consequential LCA study by Vandepaer et al [53] was found, where the avoided burden is looked upon as substitution in an open loop scheme. Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Among the studies, 15 were marked for closed-loop approximation, including both Sanfélix et al [19] and Sanfélix et al [52], who argue for substitution in their attributional study setup. In contrast, only one consequential LCA study by Vandepaer et al [53] was found, where the avoided burden is looked upon as substitution in an open loop scheme. Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, this applies in general to multi-criteria decision making (e.g., cf. [14,22,26]). On the other hand, the transparent approach helps in understanding the relations and conflicts between different goals and assists in solving the complexity of future energy systems.…”
Section: Discussionmentioning
confidence: 99%
“…On the base of the Swiss TIMES model, they calculate the environmental impact of different battery types under the consideration of system changes introduced by the batteries. The comprehensive set of impact categories under consideration is not taken account for in the objective function, but is subject to current research activities [26].…”
Section: Introductionmentioning
confidence: 99%
“…Undeniably, many publications, some of questionable quality, depicted LIBs as a global environmental issue and being an important source of pollution, with a resulting negative environmental impact. While it is true that environmental footprint of LIB manufacturing is significant, many scientific studies demonstrated the benefit of LIBs [38,[229][230][231]. Moreover, recycling of spent LIBs is an inherent and imperative solution to reduce this environmental footprint.…”
Section: Challenges and Trends For Recyclingmentioning
confidence: 99%